2016
DOI: 10.1007/s12011-016-0779-z
|View full text |Cite|
|
Sign up to set email alerts
|

How Trace Element Levels of Public Drinking Water Affect Body Composition in Turkey

Abstract: Since waterborne minerals appear in ionic form and are readily absorbed by the gastrointestinal tract, drinking water could be a crucial source of mineral intake. However, no comprehensive research has yet determined how trace elements in drinking water relate to body composition. We aimed to assess the relationship between clinically important trace elements in public drinking water and body composition in average, overweight and obese individuals in Turkey. The study's population consisted of 423 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Ingredients contained in mineral water for consumption such as magnesium [5, 6], calcium [7], or both [8] and bicarbonate [9] have demonstrated their ameliorating effects on metabolic diseases or health promoting functions through cohort studies in multiple locations worldwide. On the other hand, minerals such as nickel have parallel effects on body fat accumulation [10]. Since water must be consumed daily, the continuous intake of trace ingredients over a prolonged period could have certain effects on our physical conditions like those described above.…”
Section: Introductionmentioning
confidence: 99%
“…Ingredients contained in mineral water for consumption such as magnesium [5, 6], calcium [7], or both [8] and bicarbonate [9] have demonstrated their ameliorating effects on metabolic diseases or health promoting functions through cohort studies in multiple locations worldwide. On the other hand, minerals such as nickel have parallel effects on body fat accumulation [10]. Since water must be consumed daily, the continuous intake of trace ingredients over a prolonged period could have certain effects on our physical conditions like those described above.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Spain found that the trace element nickel in fat is the highest, highlighting the potential role of nickel in obesity and obesity-related diseases (34). Another study from Turkey directly shows a positive correlation between BMI and nickel (35). The results of Yang et al proved that men exposed to nickel were more prone to dyslipidemia and BMI ≥ 25 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Dahası içme suyu element içeriğinin, toplam enerji alımını azaltarak ya da metabolizmada değişikliğe neden olarak kilo alımına veya kilo kaybına neden olabileceği öne sürülmüştür 16 . Yapılan bir çalışmada, obezite ile ilişkili parametreler ve içme suyunda bulunan Al, Si, B ve Ni düzeyleri arasında pozitif korelasyon bulunduğu ifade edilmiştir 17 .…”
Section: Mikro Element Düzeyleri Ile çOcukların Vücut Element Kompozisyonları Arasındaki Ilişkinin Incelenmesi Amacıyla Yapıldıunclassified